Professionalism of Lecturers of the Ulumul Qur'an Course at the Islamic Communication and Broadcasting Study Programme UIN Sunan Kalijaga Yogyakarta - Suratin, Sonia Isna; Rokhimawan, M. Agung; Indriati, Anisah (Electronic Journal of Education, Social Economics and Technology, 2024)
The purpose of this essay is to examine and evaluate the professionalism of the lectures in the ulumul quran course and pinpoint areas that require improvement in order to significantly advance Islamic higher education at Yogyakarta's Sunan Kalijaga State Islamic University. This study employs a descriptive-narrative methodology and a qualitative research type. Data collection methods include reading texts from a variety of literary works, scientific articles, and laws and regulations pertaining to the subject of the study, such as Aamely Law Number 14 of 2005 Concerning Teachers and Lecturers to Determine the Professionalism of Lecturers. The study's findings show that ulumul qur'an lecturers in the Islamic communication and broadcasting study program at Sunan Kalijaga State Islamic University in Yogyakarta adhered to the professional standards set forth by Law No. 14 of 2005 Concerning Teachers and Lecturers, ensuring that lecturers "strongly reflect a professional attitude." Training, cooperation with other institutions, and institutional support can all help to enhance the development of lecturer professionalism, which will raise the standard of Islamic higher education. The significance of lecturers' professionalism can be better understood thanks to this study. Institutions can enhance professional attitudes in lectures and create training programs by identifying the components of professionalism that are already good. This will help to raise the standard of education at uin Sunan Kalijaga Yogyakarta. The professionalism of instructors in the context of studying the Ulumul Qur'an is explicitly examined in this study. The ulumul quran course and the idea of lecturer professionalism are connected in this study, providing an interdisciplinary viewpoint that can raise the standard of instruction at UIN Sunan Kalijaga Yogyakarta.